Gastrointestinal Assessment and Therapeutic Intervention for the Management of Exercise-Associated Gastrointestinal Symptoms: A Case Series Translational and Professional Practice Approach - Gaskell, Stephanie K.; Rauch, Christopher E.; Costa, Ricardo J. S. (Frontiers in Physiology, 2021)
This translational research case series describes the implementation of a gastrointestinal assessment protocol during exercise (GastroAxEx) to inform individualised therapeutic intervention of endurance athletes affected by exercise-induced gastrointestinal syndrome (EIGS) and associated gastrointestinal symptoms (GIS). A four-phase approach was applied. Phase 1: Clinical assessment and exploring background history of exercise-associated gastrointestinal symptoms. Phase 2: Individual tailored GastroAxEx laboratory simulation designed to mirror exercise stress, highlighted in phase 1, that promotes EIGS and GIS during exercise. Phase 3: Individually programmed therapeutic intervention, based on the outcomes of Phase 2. Phase 4: Monitoring and readjustment of intervention based on outcomes from field testing under training and race conditions. Nine endurance athletes presenting with EIGS, and two control athletes not presenting with EIGS, completed Phase 2. Two athletes experienced significant thermoregulatory strain (peak core temperature attained > 40°C) during the GastroAxEx. Plasma cortisol increased substantially pre- to post-exercise in n = 6/7 (Δ > 500 nmol/L). Plasma I-FABP concentration increased substantially pre- to post-exercise in n = 2/8 (Δ > 1,000 pg/ml). No substantial change was observed in pre- to post-exercise for systemic endotoxin and inflammatory profiles in all athletes. Breath H2 responses showed that orocecal transit time (OCTT) was delayed in n = 5/9 (90–150 min post-exercise) athletes, with the remaining athletes (n = 4/9) showing no H2 turning point by 180 min post-exercise. Severe GIS during exercise was experienced in n = 5/9 athletes, of which n = 2/9 had to dramatically reduce work output or cease exercise. Based on each athlete’s identified proposed causal factors of EIGS and GIS during exercise (i.e., n = 9/9 neuroendocrine-gastrointestinal pathway of EIGS), an individualised gastrointestinal therapeutic intervention was programmed and advised, adjusted from a standard EIGS prevention and management template that included established strategies with evidence of attenuating EIGS primary causal pathways, exacerbation factors, and GIS during exercise. All participants reported qualitative data on their progress, which included their previously presenting GIS during exercise, such as nausea and vomiting, either being eliminated or diminished resulting in work output improving (i.e., completing competition and/or not slowing down during training or competition as a result of GIS during exercise). These outcomes suggest GIS during exercise in endurance athletes are predominantly related to gastrointestinal functional and feeding tolerance issues, and not necessarily gastrointestinal integrity and/or systemic issues. GastroAxEx allows for informed identification of potential causal pathway(s) and exacerbation factor(s) of EIGS and GIS during exercise at an individual level, providing a valuable informed individualised therapeutic intervention approach.